2022
DOI: 10.3390/healthcare10050926
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Limpopo Province of South Africa’s Response to COVID-19: A Mixed Methods Protocol to Analyze and Share Lessons Learned

Abstract: COVID-19 is a priority health research agenda item in South Africa. The World Health Organization declared the COVID-19 outbreak as a Public Health Emergency of International Concern, which requires all countries to respond and share data with others. Responses included the implementation of measures to reduce the spread of COVID-19 and protect health systems from being overwhelmed by seriously ill patients. Each country was mandated to assess its own risk and rapidly implement the necessary measures to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This study used secondary data kept by the Limpopo Department of Health (LDoH). Ethical issues and permission to access the data are described in the published protocol [52], which was approved by Turfloop Research Ethics Committee (TREC) at UL and was granted (TREC/293/2021: IR). The study included 15,151 patient clinical records of laboratoryconfirmed COVID-19 cases.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…This study used secondary data kept by the Limpopo Department of Health (LDoH). Ethical issues and permission to access the data are described in the published protocol [52], which was approved by Turfloop Research Ethics Committee (TREC) at UL and was granted (TREC/293/2021: IR). The study included 15,151 patient clinical records of laboratoryconfirmed COVID-19 cases.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…This study used secondary data on the COVID-19 response kept by the LPDoH. The mixed-methods study protocol for the use of secondary data kept by LPDoH is reported elsewhere [ 26 ]. A quantitative study by Tshitangano et al describes, in detail, the process followed by LPDoH when collecting primary data on the COVID-19 response using a clinical mortality audit tool [ 27 ].…”
Section: Methodsmentioning
confidence: 99%